Metallothionein protein variants generated in rat liver as a result of DNA and RNA ethylations by the carcinogen diethylnitrosamine - Jauch, A.; Lutz, W.K. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1986)
Metallothionein (MT) is a protein which contains 20 cysteine residues but no aromatic amino acids. It was tested whether treatment of male rats with the hepatocarcinogen diethylnitrosamine (DENA) could ethylate nucleic acids in such a way that protein variants containing measurable amounts of aromatic amino acid residues could be isolated from the livers of treated animals. To give a low limit of detection, the “wrong” amino acid precursors were administered in radiolabelled form at high levels of activity (7 mCi/kg each of [ 3H]tyrosine and [ 3H]phenylalanine). 11 μCi/kg [ 14C]cysteine was given as an internal marker for MT biosynthesis. 6 h after amino acid administration, metallothionein (MT) was isolated from the liver and extensively purified. After acid hydrolysis and collection of Cys, Tyr, and Phe from an HPLC analysis of the amino acids, the 3H/ 14C ratio was determined. The carcinogen-treated rats exhibited a significantly higher ratio than the vehicle-treated animals. This type of in vivo assay might find interesting applications in the investigation of nucleic acid alkylations as promutagenic lesions.